Spurring or Blurring Journalism & Mass Communication Quarterly 1–32 © 2024 AEJMC Professional Standards? The Role of Digital Technology in Implementing Journalistic Role Ideals in Contemporary Newsrooms (2024)
This study examines the perceived relevance and implementation of competing normative ideals in journalism in times of increasing use of digital technology in newsrooms. Based on survey and content analysis data from 37 countries, we found a small positive relationship between the use of digital research tools and “watchdog” performance. However, a stronger and negative relationship emerged between the use of digital audience analytics and the performance of “watchdog” and “civic” roles, leading to an overall increase in conception–performance gaps on both roles. Moreover, journalists’ use of digital community tools was more strongly and positively associated with “infotainment” and “interventionism.”